ANALISIS KEBUTUHAN SISTEM WEBSITE COMPANY PROFILE PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS DINAMIKA - Yonatan Koentjoro, Edo; Oktaviani, Oktaviani; Mirza Maulana, Yoppy (JURNAL ILMIAH INFORMATIKA, 2024)
The Higher Education Research and Community Service Institute (“Lembaga Penelitian dan Pengabdian kepada Masyarakat” as known as LPPM) is one of the academic elements in the Tridarma of Higher Education. The main task of LPPM is to plan, implement, coordinate, monitor and assess the implementation of research and community service (“Pengabdian kepada Masyarakat” as known as PkM) activities. Any information in the form of announcements and news about research and PkM needs to be distributed to lecturers and academic circles. A platform is needed in the form of a website that can convey this information. Currently, the Center for Research and Community Service (“Pusat Penelitian dan Pengabdian kepada Masyarakat” as known as P3kM) at Dinamika University (Undika) still does not have a website to accommodate this information. The information and news obtained by P3kM is conveyed via the Whatsapp group platform and e-mail. So this information is sometimes difficult to find again if needed. Based on these problems, researchers plan to analyze the needs of the Undika P3kM website which will later be built in subsequent research.